Bisphenol AF compromises blood-testis barrier integrity and sperm quality in mice. (December 2019) - Wu, Di; Huang, Chun-Jie; Jiao, Xiao-Fei; Ding, Zhi-Ming; Zhang, Shou-Xin; Miao, Yi-Liang; Huo, Li-Jun
Abstract: The profound influence of environmental chemicals on human health including inducing life-threatening gene mutation has been publicly recognized. Being a substitute for the extensively used endocrine-disrupting chemical BPA, Bisphenol AF (BPAF) has been known as teratogen with developmental toxicities and therefore potentially putting human into the risk of biological hazards. Herein, we deciphered the detrimental effects of BPAF on spermatogenesis and spermiotiliosis in sexual maturity of mice exposing to BPAF (5, 20, 50 mg/kg/d) for consecutive 28 days. BPAF exposure significantly compromises blood-testis barrier integrity and sperm quantity and quality in a dose-dependent manner. Sperms from BPAF exposure mice are featured by severe DNA damage, altered SUMOylation and ubiquitination dynamics and interfered epigenetic inheritance with hypermethylation of H3K27me3 presumably due to the aggregation of cellular reactive oxygen species (ROS). Furthermore, BPAF treatment (50 μM for 24 h) compromises cytoskeleton architecture and tight junction permeability in primary cultured Sertoli cells evidenced by dysfunction of actin regulatory proteins (e.g. Arp3 and Palladin) via activation of ERK signaling, thereby perturbing the privilege microenvironment created by Sertoli cells for spermatogenesis. Overall, our study determines BPAF is deleterious for male fertility, leading to a better appreciation of its toxicological features in our life. Highlights: BPAF exposure compromises sperm production and quality and disrupts the post-translational modifications of sperm. BPAF exposure significantly compromises blood-testis barrier integrity both in vivo and in vitro. BPAF perturbs the cytoskeleton architecture via activation of ERK1/2 signaling.